Invasive Aspergillosis in a Renal Transplant Recipient Successfully Treated with Interferon-Gamma. (27th September 2012) - Estrada, C.; Desai, A. G.; Chirch, L. M.; Suh, H.; Seidman, R.; Darras, F.; Nord, E. P.
Abstract : Invasive aspergillosis is a serious complication of solid organ transplantation. An early diagnosis is hampered by the lack of reliable serum markers and, even if appropriately diagnosed and treated with current antifungal agents, has a high mortality rate. We report a case of invasive pulmonary and cerebral aspergillosis in a renal transplant patient treated with IFN- γ in conjunction with combination anti-fungal therapy for six weeks in whom complete resolution of the fungal infection was achieved. Renal function remained intact throughout the treatment period. Surveillance CT scans of the chest and head showed resolution of prior disease but revealed a new left upper lobe mass four months after completion of treatment with IFN- γ . Biopsy of the lesion was positive for primary lung adenocarcinoma, for which she underwent left upper lobe resection. The pathology report confirmed clear surgical margins and lymph nodes and no evidence of fungal hyphae. IFN- γ should be considered early in the management of invasive aspergillosis in renal transplant patients. To date, allograft rejection has not been encountered.